Control of the obscure mealybug, Pseudococcus viburni (Hemiptera: Pseudococcidae) using entomopathogenic fungi and nematodes - Mathulwe, Letodi Luki (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDConsEcol)--Stellenbosch University, 2021.